Clinical and cytological findings in oral cavity of young shisha smokers and non-smokers - a comparative study - Ramamurthy Priyadarshini Hesarghatta; Fernandes Bennete Aloysius; Tegginamani Anand S.; Rath Avita; Sidhu Preena; Bin Zamzuri Ahmad Termizi (EDP Sciences, 2022)
Introduction: Shisha, a form of smoking tobacco is known to be detrimental to oral health. Yet, the effects of shisha on oral health is not well documented. Hence, this study was undertaken to compare the clinical and cytological findings in oral cavity of young shisha smokers as compared to non-smokers. Materials and methods: A cross-sectional analytical study was undertaken among 60 subjects including 30 young shisha smokers and 30 non-smokers. Clinical examination was carried out to record gingival status, periodontal status, oral hygiene and dental caries experience. Exfoliative cytology was used to study the cytological changes of buccal mucosal cells. Data was analysed using SPSS version 22. Student's t-test, Fisher's exact test and odd's ration was used for comparison. p < 0.05 was considered statistically significant. Results: No significant differences were found between the groups with respect to proportion of subjects with gingivitis (p = 0.071), erosion (p = 0.085) and dental caries experience (p = 0.329). However, shisha smokers had poorer oral hygiene and more severe gingival inflammation as compared to non-smokers with p = 0.026 and p = 0.007 respectively. The odds of having atypical cells in oral mucosa among shisha smokers was 3.76 times higher than the non-smokers. Conclusion: The findings of our study showed that young shisha smokers had more atypical cells in oral mucosa as compared to their non-smoking counterparts. However, longitudinal studies are needed to affirm the findings of this study.